PENGARUH VALUE BASED PRICING TERHADAP KEPUTUSAN BERKUNJUNG DI TAMAN REKREASI KOTA BUNGA CIANJUR (Survei terhadap Wisatawan Nusantara Taman Rekreasi Kota Bunga Cianjur) - Silalahi, Apriani; Andari, Rini (THE Journal : Tourism and Hospitality Essentials Journal, 2011)
Kabupaten Cianjur is one of regencies in West java has tourism potential can be relied, and the one of destination is Taman Rekreasi Kota Bunga. Taman Rekreasi Kota Bunga is a recreation area that offers a variety of tourist attraction with the unique feel for the tourist. The number of tourist visits on Taman Rekreasi Kota Bunga has increase from 2008 to 2010. Value based pricing is one of marketing strategy that can be used to increase the number of visit. In connection with these to research studies conducted on the influence value based pricing toward visiting decision Taman Rekreasi Kota Bunga. The purpose of this research is to find value based pricing influence visiting decisions to Taman Rekreasi Kota Bunga. Value based pricing consists of discounting, penetration pricing, value pricing, market segmen pricing. Technique of sampling is systematic random sampling. The method in that used in this research is explanatory survey by using ordinal scale. Analyze from this research use Path Analysis with a computer software tools SPSS 19.0. The result of this research is value based pricing influence significantly 86,6% and the rest influence other factors. Based on the result of statistical test results were obtained, there were four variables of value based pricing which had an influence on visiting decisions of discounting, penetration pricing, market segmen pricing and there was one variables that had no effect on visiting decisions was value pricing. That it can be concluded that direct discounting, penetration pricing, market segmen pricing strong influence the visiting decision on Taman Rekreasi Kota Bunga.